2020
DOI: 10.25179/tjem.2020-74287
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Thyroid Antibodies at the Diagnosis of Subacute Thyroiditis

Abstract: Objective: Although subacute thyroiditis (SAT) is not an autoimmune disease, the presence of antithyroid antibodies has been reported in this disease too. This study aims to determine the frequency of antithyroid antibodies at the time of diagnosis of SAT. Material and Methods: Quantitative measurements of antithyroid peroxidase antibody (anti-TPO), antithyroglobulin antibody (anti-Tg), and thyroid-stimulating hormone (TSH) receptor autoantibodies (TRAb) were made in 76 patients at the diagnosis of SAT. Cytopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Analysis of a large population of classical SAT revealed that the frequency of positivity of ATPO was found as 7.8% 32 . In another study, it was found a little bit higher as 11.8% 33 . We could not measure thyroid autoantibodies in all patients, but at least one of them was positive in approximately one fifth of the patients in Vac-SAT, and no difference was found among the groups.…”
Section: Discussionmentioning
confidence: 84%
“…Analysis of a large population of classical SAT revealed that the frequency of positivity of ATPO was found as 7.8% 32 . In another study, it was found a little bit higher as 11.8% 33 . We could not measure thyroid autoantibodies in all patients, but at least one of them was positive in approximately one fifth of the patients in Vac-SAT, and no difference was found among the groups.…”
Section: Discussionmentioning
confidence: 84%
“…In such scintigraphic limitations, TSH receptor antibodies are helpful in distinguishing GD from other conditions. However, there may be false-negative and false-positive results (8,9). A total T3/total T4 ratio of <20 ng/mcg in thyrotoxic patients is considered an indicator of destructive thyrotoxicosis (7).…”
Section: Introductionmentioning
confidence: 99%